The Provision of Communication and Emotional Support by Drug Swallowing Supervisors (DSS) in the Treatment Success of Pulmonary Tuberculosis - Ferani Nasution; Reni Aprinawaty Sirait; Karnirius Harefa (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2026)
Pulmonary tuberculosis (TB) remains a major public health concern, with treatment success rates that have not yet reached optimal levels. The success of TB treatment is not solely determined by the availability of anti-tuberculosis drugs, but is also influenced by the quality of support provided by Drug Swallowing Supervisors (DSS), particularly in terms of communication and emotional support. This study aimed to analyze the effect of DSS communication and emotional support on the success of pulmonary TB treatment at the Simangalam Public Health Center in 2025. This study used an explanatory research design with a cross-sectional approach and was conducted from October to December 2025. The study population consisted of 327 pulmonary TB patients, with a sample of 150 respondents selected through purposive sampling. Data were collected using structured questionnaires and medical records. Data analysis included univariate descriptive analysis, bivariate analysis using the chi-square test, and multivariate analysis using binary logistic regression with a 95% confidence level. The results showed that the treatment success rate of pulmonary TB was 64.0%. DSS communication had a statistically significant effect on treatment success (p-value=0.001; OR=6.644), , indicating that good communication increased the likelihood of successful treatment by approximately seven times. In contrast, emotional support did not show a significant effect. Effective communication plays a crucial role in improving patient adherence, whereas the limited impact of emotional support may be due to the long duration of TB treatment, reducing its effectiveness if not provided consistently. In conclusion, DSS communication is the most influential factor in the success of pulmonary TB treatment. It is recommended that public health centers enhance DSS capacity through training and implement standardized communication procedures.